Transformation of Learning in Madrasah through Innovations in Developing Environmental Care Character for Future Generations - Gitmiwati Gitmiwati; Indrayuda Indrayuda (STAI Hubbulwathan Duri, 2024)
This research explores pioneering innovations aimed at promoting environmental stewardship in Madrasah Ibtidaiyah, emphasizing the critical need to integrate sustainable living and environmental management in early education. A key innovation is the adoption of project-based learning, where students engage in practical activities such as developing community gardens and managing waste. These initiatives, along with curriculum enhancements that incorporate ecological principles into religious studies, provide a comprehensive framework for environmental education. The study examines various pedagogical strategies, including interactive ecology-based storytelling and curriculum modifications that introduce environmental themes into Islamic studies. Additionally, it highlights community engagement efforts, such as collaboration between parents and teachers in environmental initiatives. These methods are analyzed to determine how they successfully instill a profound sense of environmental responsibility in students, transforming abstract concepts into actionable practices in their daily lives. Furthermore, the research addresses challenges faced by educators in aligning environmental education with the religious and cultural contexts of Madrasah Ibtidaiyah, ensuring compatibility with Islamic values while fostering global ecological awareness. Through a thorough review of contemporary practices, this study identifies successful models and best practices that shape environmental care character. The findings offer valuable insights for educators, administrators, policymakers, and curriculum developers, potentially influencing future educational policies and the design of curricula. This research underscores the vital role Madrasah Ibtidaiyah can play in cultivating environmentally conscious citizens and promoting sustainable ecological management at local and global levels.